2017
DOI: 10.18203/2349-3291.ijcp20170709
|View full text |Cite
|
Sign up to set email alerts
|

A study of dermatoses in patients attending pediatric OPD in a tertiary care hospital of Gandhinagar, Gujarat, India

Abstract: Background: Skin diseases in paediatric population are common all over the world. There is a wide variation in the presentation of Dermatoses in various studies. The variation among dermatoses can possibly be due to region of study, prevalent environmental factors, type of population studied, and hygiene and nutritional status and environmental factors. The objective of this study was to study prevalence, pattern of presentation and aetiologies of various dermatoses in paediatrics.Methods: A prospective, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…(36.8%) most frequently followed by viral (17.4%), parasitic infections (10.2%) and fungal infections (5%) in their study, 12 Mustafa et al recorded 45.9% bacterial infections followed by viral (32.03%) and fungal (22.02%) infections, 17 however study by Javed showed fungal infections (15.7%) to be more frequent followed by bacterial infections (8.2%), 14 Rabia et al documented fungal infections (48.7%) to be most common followed by viral (33.5%) and then bacterial (17.7%), 3 These differences may be attributed to seasonal and climatic variations, pyoderma was the most common bacterial infection (35.29%) observed in this study population followed by impetigo (28.34%) and folliculitis (26.20%), Mustafa at al found impetigo (94%) to be the most frequent bacterial infection, Javed et al recorded impetigo (58%), furunculosis( 26%), folliculitis(9%), ecthyma (7%) as the common bacterial infections in the descending pattern, 17 Balai observed impetigo (59.57%) most frequently occurring bacterial infection followed by pyoderma (26.39%), 9 Geet also found pyoderma (22.20%) as the most common dermatoses in their study group" (n= 500). 12 Measles (38.27%) was widely spreading after varicella (30.8%), molluscum contagiosum (23.45%) in this study. Rabia et al observed warts (52.8%) as the frequently occurring viral infection followed by molluscum contagiosum (20.8%).…”
Section: Non-inective Dermatoses Infective Dermatosesmentioning
confidence: 69%
See 2 more Smart Citations
“…(36.8%) most frequently followed by viral (17.4%), parasitic infections (10.2%) and fungal infections (5%) in their study, 12 Mustafa et al recorded 45.9% bacterial infections followed by viral (32.03%) and fungal (22.02%) infections, 17 however study by Javed showed fungal infections (15.7%) to be more frequent followed by bacterial infections (8.2%), 14 Rabia et al documented fungal infections (48.7%) to be most common followed by viral (33.5%) and then bacterial (17.7%), 3 These differences may be attributed to seasonal and climatic variations, pyoderma was the most common bacterial infection (35.29%) observed in this study population followed by impetigo (28.34%) and folliculitis (26.20%), Mustafa at al found impetigo (94%) to be the most frequent bacterial infection, Javed et al recorded impetigo (58%), furunculosis( 26%), folliculitis(9%), ecthyma (7%) as the common bacterial infections in the descending pattern, 17 Balai observed impetigo (59.57%) most frequently occurring bacterial infection followed by pyoderma (26.39%), 9 Geet also found pyoderma (22.20%) as the most common dermatoses in their study group" (n= 500). 12 Measles (38.27%) was widely spreading after varicella (30.8%), molluscum contagiosum (23.45%) in this study. Rabia et al observed warts (52.8%) as the frequently occurring viral infection followed by molluscum contagiosum (20.8%).…”
Section: Non-inective Dermatoses Infective Dermatosesmentioning
confidence: 69%
“…(M: F = 1.59:1) and Javed et al showing 65% males and 35% females. 12,14 The most commonly observed "dermatoses in this study were infections and infestations (68%), the similar results were found in many other studies like by Khalid A et al (63.2%), Thakare S et al (46.33%), Geet et al ( 69.4% ), Rabia et al found (75.1%) and Balai (40.60%), 3,12,15,16 Mustafa et al recorded that out of 1860 patients 949 (51.02%) had infections and 388 (20.9 %) had infestations". 17 In this study, "Bacterial infections were the most common (36.45%) followed by viral (15.78%), parasitic (7.99%) and fungal infections (7.79%), Geet et al also observed bacterial infections 31.96%, 32% 68.03%, 68% 0, 0% 0, 0%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Infections were the commonest reported dermatosis in Gunjana et al study (59.2%) which is nearly similar to our study (54.64%). 7 Figueroa et al reported skin infestations to be more common among school children in rural Ethiopia. 8 The high prevalence of pyogenic bacterial skin infection (40.27%) was reported by Sabyasachi et al study and also by Ghosh et al (35.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Page 818Viral infections included Hand foot mouth disease (HFMD) which dominated the viral infection group with 23 cases followed by chicken pox (10), Wart (9), Molluscum contagiosum(7) and Herpes zoster (3). Fungal infections included Dermatophytosis and Pityriasis versicolor with 42 cases and 8 cases respectively (…”
mentioning
confidence: 99%